Marriage Agreement on Common Property in Marriage (Comparative Study of Indonesia and The United States) - Handayani, Wiwid Putri; Cahyaningsih, Diana Tantri (Fakultas Syariah INSURI Ponorogo, 2024)
This article compares Indonesia and the United States to discuss a prenuptial agreement for joint marital assets. Indonesia adheres to a civil law legal system by basing prenuptial agreement on Article 29 of the Marriage Law. Meanwhile, the United States, which adheres to a standard legal system, implements the Uniform Premarital and Marital Agreements Act (UPMAA). The research method used in this writing is legal research with a statutory approach and a comparative approach. The results of this research are the reasons for making a prenuptial agreement, among others, because the agreement will facilitate the division of assets, which will benefit both parties in the event of a divorce and as a step to prevent conflicts from arising in the future. The difference between prenuptial agreements between Indonesia and the United States is that for prenuptial agreements in Indonesia, each couple can freely determine the contents of the prenuptial agreement as long as it does not conflict with law, religion, decency, decency, or public order. Meanwhile, in the United States, each couple has specific restrictions regarding what can and cannot be written in the prenuptial agreement. So, freedom in making prenuptial agreements is still bound and limited to specific points.